Coupled Phylogenetic and Functional Enrichment in the Tomato Rhizosphere Microbiome - Silvia Talavera-Marcos; Ramón Gallego; Rubén Chaboy-Cansado; Alberto Rastrojo; Daniel Aguirre de Cárcer (Phytobiomes Journal)
Plant–microbe interactions occur mainly in the rhizosphere, a hot spot of microbial activity and diversity, and the outcome of these interactions can significantly affect plant productivity. A better understanding of the rhizosphere microbiome is, therefore, required to develop successful knowledge-based microbiome modification strategies that help improve plant productivity. Here, we investigated the community assembly process of the tomato rhizosphere microbiome and its potential composition–function relationships through the lens of a conceptual framework based on the phylogenetically constrained assembly of microbial communities. In this study, we grew tomato plantlets on different soil types with high replication and assessed community composition using high-throughput sequencing of the 16S rRNA bacterial marker gene and community function based on the predicted minimal metagenome of the microbial ecosystem. We also conducted additional computer simulations to examine the relationship between phylogenetic clustering and community function. We observed a systematic enrichment in the rhizosphere in terms of phylogeny and predicted functional content and were able to delimit the phylogenetic signal in the ecosystem owing to the presence of 12 functionally coherent phylogenetic core groups in all samples. These groups, which accounted for a large fraction of the total community, belonged to the Alpha, Beta, and Gammaproteobacteria, Actinobacteria, and Bacilli classes and presented exclusive functions related to important ecosystem services. Furthermore, our analyses indicated that these groups accounted for a large proportion of the ecosystem's predicted minimal metagenome. Overall, our study suggests that community assembly followed coupled phylo-functional selection, a phenomenon that likely occurs in other rhizosphere microbiomes. This knowledge not only advances our understanding of how community composition–phylogeny–function relationships drive the assembly process of the rhizosphere microbiome but also will help guide the design of synthetic rhizosphere microbiomes for both research and commercial purposes. [Figure: see text] Copyright © 2025 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.